Cost-Effective Production of Methane from Commonly Available Food wastes in China: A Comprehensive Review and Comparative Analysis (Journal of Agriculture and Biology, 2025)
Anaerobic digestion or biogas technology represents a viable approach to addressing existing problems with the disposal and treatment of organic waste where organic substances are converted to methane, a source of renewable energy. The quarterly review paper covers all facets of methane generation from organic waste, especially the functional model and performance of AD systems in China’s diversified industries. In the paper, the author divides AD systems into four sections: batch, continuous, single-stage, and multi-stage, and explains the best practices of each for large-scale operations as well as for certain types of waste. Technical problems, high moisture content, foaming, and the problem of acidification are described along with their influence on the effectiveness of the process and with reference to ways to avoid these problems. Economic challenges are also addressed, with an emphasis on the costs associated with scaling up AD systems from pilot to full-scale operations, the economic viability of these systems, and the barriers to technology adoption. Case studies from various regions in China are examined to demonstrate the practical applications and the potential of these systems to contribute to energy sustainability and waste reduction. The paper concludes with recommendations for future research and development to enhance the efficiency and cost-effectiveness of methane production from organic waste, underscoring the need for technological innovations and supportive policies.